Anthropogenic changes to leaf litter input affect the fitness of a larval amphibian. (3rd May 2013) - Stephens, Jeffrey P.; Berven, Keith A.; Tiegs, Scott D.
Summary Human activities, invasive species and climate change have altered the composition of native forest plant communities in North America. These changes have, in turn, altered the composition of leaf litter in woodland ponds with consequences for the organisms they harbour, such as amphibian larvae. We used mesocosms to assess how 10 species of allochthonous litter, which differ in their regional abundance and chemical composition, affect ephemeral ponds. We were particularly interested in effects on larval amphibian fitness, including metamorphic mass, larval period and survival. Litter had strong effects on the fitness of larval wood frogs (Lithobates sylvaticus), water chemistry, and phytoplankton and periphyton biomass in the mesocosms. Litter from green ash (Fraxinus pennsylvanica), a tree species in decline, enabled frog larvae to grow larger, develop faster and survive better than larvae from other litter treatments. Interestingly, three invasive wetland plant species produced heavy metamorphs, with shorter larval periods and higher survival relative to native wetland plants. Litter from red maple (Acer rubrum, now among the most abundant native trees in the eastern United States), cattail (Typha latifolia) and sedge (Carex stricta) produced metamorphs that were small and survived poorly. Mass at metamorphosis was best explained by litter quality (carbon, nitrogen and phosphorus content) and primary producer biomass, while survival and larval period were best explained by a combination of litter quality, primary producer biomass and water chemistry (polyphenolics and pH). Additionally, litter quality and primary producer biomass explained differences in the elemental composition of metamorphs. Lastly, our data suggest that litter nitrogen may be a limiting resource that affects the export of metamorphic frog biomass from ephemeral ponds. Overall, our results indicate that anthropogenic changes in plant communities lead to changes in the quality of allochthonous litter input and strongly affect amphibian fitness.